Simple mono-halogenated perylene diimides as non-fullerene electron transporting materials in inverted perovskite solar cells with ZnO nanoparticle cathode buffer layers. Issue 25 (23rd May 2017) - Wu, Jhao-lin; Huang, Wen-Kuan; Chang, Yu-Chia; Tsai, Bo-Chou; Hsiao, Yu-Cheng; Chang, Chih-Yu; Chen, Chin-Ti; Chen, Chao-Tsen
Abstract : Mono-halogenated perylene diimides as solution-processable electron transporting layers in perovskite solar cells with ZnO nanoparticle cathode buffer layers. Abstract : We have synthesized and characterized three perylene diimides, X-PDI, whereX =H, F, orBr . These three compounds have been tested for the substitution of [6, 6]-phenyl C61 butyric acid methyl ester (PC61 BM) in inverted perovskite solar cells (PVSCs). Although the efficiency of PDI derivative-based conventional PVSCs is as high as 17.6% ( J. Mater. Chem. A, 2016, 4, 8724), the corresponding performance of inverted PVSCs is still lagging behind and improvement is necessary. For electron accepting (from CH3 NH3 PbI3 perovskite) and electron transporting properties of the materials, UV-visible absorption spectroscopy, electrochemical cyclic voltammetry, direct current conductivity, space-charge limited current (SCLC) electron mobility, atomic force microscopy (AFM) surface morphology, and photoluminescence (PL) spectroscopy gauging charge-trapping have been studied. The HOMO/LUMO energy levels are 5.94/4.00, 5.83/3.96, 6.00/3.97, and 5.48/3.73 eV forH-PDI, F-PDI, Br-PDI, and PC61 BM, respectively. Direct current conductivities ofH-PDI, F-PDI, Br-PDI, and PC61 BM are 8.71 × 10 −8, 1.18 × 10 −9, 2.2 × 10 −6, and 8.42 × 10 −6 S cm −1, respectively. The SCLC electron mobility ofH-PDI, F-PDI, Br-PDI, and PC61 BM are 1.12 × 10 −4, 8.31 × 10 −6, 1.08 × 10 −3, and 5.00 × 10 −3 S cm −1, respectively. PL spectroscopy of CH3 NH3 PbI3 perovskite provides emission at wavelength of 781 nm, which is the same as for the perovskite layer covered with a thin film ofH-PDI orF-PDI . However, the emission wavelength was blue-shifted to 773–774 nm when the perovskite layer was covered with a thin film ofBr-PDI or PC61 BM. Using UV-visible absorption spectroscopy, the solubility (in chloroform) was determined as 1.2 × 10 −2, 8.7 × 10 −2 and >10 −1 mol L −1 forF-PDI, H-PDI, andBr-PDI, respectively. In thin film state, UV-visible absorption spectroscopy indicated that the extent of molecular aggregation wasF-PDI ≫H-PDI >Br-PDI, which is consistent with the AFM-estimated root-mean-square roughness ofF-PDI >H-PDI >Br-PDI ∼ PC61 BM. Without the solution processed ZnO NP cathode buffer layer (CBL), the power conversion efficiency (PCE) ofH-PDI, F-PDI, Br-PDI, and PC61 BM PVSCs is ∼1%, ∼0%, 3.2%, and 4.1%, respectively. With the ZnO NP CBL, PCE is ∼7.8%, ∼0%, 10.5%, and 11.1% forH-PDI, F-PDI, Br-PDI, and PC61 BM PVSCs, respectively. Through this study, we have demonstrated that the simple mono-bromine substituted perylene diimide (Br-PDI ), is solution processable and has potential for use as a non-fullerene electron accepting and electron transporting material in inverted PVSCs.